The unequal incidence of non-standard employment across occupational groups: An empirical analysis of post-industrial labour markets in Germany and Europe - Paul Marx (Institute for the Study of Labor (IZA), 2011)
The paper addresses an often neglected question in labour market research: to which extent do outcomes aggregated on the national level disguise occupational diversity in employment conditions? In particular, how and why do occupational groups differ with regard to the incidence of non-standard employment? To explore these questions, the paper derives a detailed occupational scheme from the literature, capturing the variety of labour market outcomes within countries. In a second step, the scheme is theoretically linked to the topic of non-standard work. It is argued that different degrees of skill specificity across occupational groups produce diverging incentives for flexible and long-term employment, respectively. This leads to the expectation of (some) service-sector occupations showing stronger tendencies towards non-standard employment than those in the industrial sector. Based on European and German micro data, the categorisation is used to decompose various labour market indicators. The results clearly demonstrate the unequal incidence of non-standard employment along the lines of the suggested categorisation. Moreover, the longitudinal perspective suggests that traditionally functioning occupational groups will be crowded out by more destandardised ones.
urn:nbn:de:101:1-201104113948
Keywords: J21; J24; J31; 330; temporary employment; low-pay; labour market dualisation; occupational groups; post-industrial labour markets; Germany; Befristeter Arbeitsvertrag; Ungeschützte Beschäftigung; Dualer Arbeitsmarkt; Berufsstruktur; Niedriglohn; Dienstleistungsgesellschaft; Deutschland; Europa